Purification and Characterization of Alkaline Protease Enzyme from Bacillus cereus LS2B - junaidi, Yendri (2016)
Alkaline protease enzyme from Bacillus cereus LS2B was successively purified by three steps procedure including ammonium precipitation, membrane dialysis, and HiTrap ion exchange chromatography with DEAE Sepharose FF matrix. The best enzyme concentration was obtained by precipitation using 80% of ammonium sulfate concentration. Observing the various levels of the enzyme concentration was significantly (p> 0.05) increased the activity of the enzyme, whereas the highest activity was found in the enzyme with 100% of protein concentration (without dilution). The collection of tyrosine, through the technique of centrifugation and filtration techniques, was not significant effect on the enzyme activity. Characteristics of the HiTrap ion exchange chromatography machine was set at flow rate 1.5 ml min-1. The specific activity of the crude enzyme, ammonium sulfate, membrane dialysis and HiTrap ion exchange were observed 0.4 U/mg, 0.5 U/ml, 1, 8 U/mg and 7.2 U mg, respectively. At the step of purification using HiTrap ion exchange chromatography, the alkaline protease enzyme has increased the degree of purity 16 fold from the crude enzyme. Furthermore, the protein yield was decreased from 100% from crude enzyme to 2% by HiTrap ion exchange purification. The purified enzyme was characterized using SDS-PAGE resulted in three bands of protein molecules which correspond to 34 kDa, 17 kDa, and 13 kDa molecular weight.